Metallographic corrosive liquid for Ti45Nb alloy and corrosion method

By using a metallographic corrosion solution composed of 73-77% hydrofluoric acid and 23-27% nitric acid, combined with specific sample treatment and corrosion steps, the problem of difficult metallographic corrosion of Ti45Nb alloy is solved, and the structure after corrosion is clear and the corrosion effect is achieved.

CN119800363APending Publication Date: 2025-04-11ZIGONG HANGRUI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510035874.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The metallographic corrosion of Ti45Nb alloy is difficult, especially in the large deformation extrusion state and annealed state. The existing corrosion liquids and methods cannot effectively corrode, resulting in poor tissue artifacts and corrosion effects.

Method used

A metallographic corrosion liquid is provided, which includes 73-77% hydrofluoric acid and 23-27% nitric acid according to volume percentage, and adopts specific sample treatment and corrosion steps, including grinding, polishing, cleaning and drying, and finally using degreased cotton to wipe the corrosion liquid for wiping and corrosion.

Benefits of technology

It has achieved effective corrosion of Ti45Nb alloy. The metallographic structure after corrosion is clear, easy to distinguish, good corrosion effect, no pollution, high corrosion efficiency, and is suitable for practical work applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800363A_ABST
    Figure CN119800363A_ABST
Patent Text Reader

Abstract

The invention discloses a metallographic etchant for a Ti45Nb alloy and a corrosion method, and relates to the technical field of titanium-niobium alloys. The metallographic etchant for the Ti45Nb alloy comprises the following raw material components in percentage by volume: 73 to 77 percent of hydrofluoric acid and 23 to 27 percent of nitric acid. The corrosion method comprises the following steps of sample treatment, metallographic phase corrosion liquid preparation and metallographic phase corrosion. The problem that a large-deformation extrusion state and annealing state Ti45Nb alloy metallographic specimen is difficult to corrode can be solved, and the corroded metallographic structure is clear and easy to distinguish and analyze. The metallographic etchant is simple in component, and the corrosion method is convenient to operate, stable, reliable and good in corrosion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of titanium-niobium alloys, and in particular to a metallographic etching solution and an etching method for Ti45Nb alloy. Background Art

[0002] Ti45Nb alloy has excellent machining properties and low-temperature superconductivity, and is the best material choice for rivets used in composite material connections. Its plasticity and the high strength of Ti6A14V form a perfect combination. The bimetallic titanium alloy rivet composed of Ti6A14V nail rod and Ti45Nb head is suitable for the connection of titanium alloy components and composite materials of various aircraft.

[0003] Ti45Nb alloy is a high-niobium metastable β-type titanium alloy. The high niobium content significantly improves the corrosion resistance of Ti45Nb. After rough grinding, fine powder and mechanical polishing, a layer of sticky substances is easily produced on the surface of the sample, making it more difficult to corrode the metallographic sample of Ti45Nb alloy, and even causing a false organization. Although the metallographic etching solution of titanium alloy is generally prepared with hydrofluoric acid, nitric acid and water in a certain volume percentage, Ti45Nb alloy is not sensitive to general etching solutions, such as Kroll etching solution.

[0004] There are few reports on the preparation method and corrosion method of Ti45Nb alloy corrosion solution in the current corrosion technology. Therefore, it is particularly important to develop the metallographic corrosion solution and its preparation method and corrosion method of Ti45Nb alloy to make the corrosion effect and microstructure display effect of Ti45Nb alloy good, which will also promote the research of Ti45Nb alloy. Summary of the invention

[0005] The purpose of the present application is to provide a metallographic etching liquid and etching method for Ti45Nb alloy, which can solve the problem of difficult etching of Ti45Nb alloy metallographic samples in large deformation extrusion state and annealing state, and the metallographic structure after etching is clear and easy to distinguish. The metallographic etching liquid has simple components, and the etching method is easy to operate, stable and reliable, and has good etching effect.

[0006] The technical solution of this application is as follows:

[0007] On the one hand, an embodiment of the present application provides a metallographic etching solution for Ti45Nb alloy, and its raw materials include the following components by volume percentage: 73-77% hydrofluoric acid and 23-27% nitric acid.

[0008] Furthermore, in some embodiments of the present application, the hydrofluoric acid and the nitric acid are both analytical grade reagents.

[0009] Furthermore, in some embodiments of the present application, the raw materials include the following components by volume percentage: 75% hydrofluoric acid and 25% nitric acid.

[0010] Furthermore, in some embodiments of the present application, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of nitric acid is 68%.

[0011] On the other hand, the embodiment of the present application also provides a corrosion method for Ti45Nb alloy, which uses the above-mentioned metallographic etching solution and includes the following steps:

[0012] Sample treatment: Take a Ti45Nb alloy sample, grind, polish, clean, and dry its surface in sequence to obtain a sample to be corroded;

[0013] Preparation of metallographic etching solution: Take hydrofluoric acid and nitric acid, add hydrofluoric acid to nitric acid in proportion, and stir to obtain metallographic etching solution;

[0014] Metallographic etching: The surface of the sample to be corroded is corroded using the metallographic etching solution, and then cleaned and dried.

[0015] Furthermore, in some embodiments of the present application, in the above sample processing step, when grinding, first use 120-800 mesh water sandpaper for coarse grinding, and then use 1200-200 mesh water sandpaper for fine grinding.

[0016] Furthermore, in some embodiments of the present application, in the above-mentioned sample processing step, when grinding, first use 120 mesh, 240 mesh, 600 mesh, and 800 mesh water sandpaper for coarse grinding, and then use 1200 mesh and 2000 mesh water sandpaper for fine grinding.

[0017] Furthermore, in some embodiments of the present application, in the above-mentioned sample processing step, during polishing, a diamond polishing spray and a velvet polishing fabric are used to polish the ground sample to be corroded.

[0018] Furthermore, in some embodiments of the present application, in the above-mentioned sample processing step, when polishing, first use a diamond polishing spray with a particle size of 5μm and a velvet polishing fabric to polish the grinded sample to be corroded so that there are no scratches caused by grinding on the polished surface, and then use diamond polishing sprays with particle sizes of 3μm and 1μm in turn, combined with velvet polishing fabric to polish the sample to be corroded so that the polished surface achieves a mirror effect.

[0019] Furthermore, in some embodiments of the present application, in the above-mentioned metallographic etching step, absorbent cotton is used to dip into the prepared metallographic etching solution, and the surface of the sample to be corroded is wiped and corroded.

[0020] Furthermore, in some embodiments of the present application, in the above metallographic etching step, the wiping etching time is 6 to 12 seconds.

[0021] Furthermore, in some embodiments of the present application, in the above metallographic etching step, after the etching is completed, it is first rinsed with water, then rinsed with anhydrous ethanol, and then blown dry.

[0022] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:

[0023] In view of the above aspects, the embodiments of the present application provide a metallographic etching liquid and a corrosion method for Ti45Nb alloy. The metallographic etching liquid has a reasonable and simple component formula and is easy to prepare. It has a good corrosion effect on the Ti45Nb alloy and has high pollution-free corrosion efficiency. The Ti45Nb alloy after corrosion has clear grains, high surface contrast, and is easy to use. The corrosion method has a simple step flow, is easy to operate, has good stability, helps to improve the efficiency of the corrosion operation, and is conducive to practical work applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is an optical microscope photo of the Ti45Nb alloy sample in the comparative example of this application;

[0026] Figure 2 This is a microstructure photograph of the annealed Ti45Nb alloy sample after corrosion in Example 1 of the present application;

[0027] Figure 3 This is a microstructure photograph of the Ti45Nb alloy sample after corrosion in the large deformation extrusion state of Example 1 of the present application;

[0028] Figure 4 This is a microstructure photograph of the annealed Ti45Nb alloy sample after corrosion in Example 2 of the present application;

[0029] Figure 5 This is a microstructure photograph of the Ti45Nb alloy sample after corrosion in the large deformation extrusion state of Example 2 of the present application;

[0030] Figure 6 This is a microstructure photograph of the annealed Ti45Nb alloy sample after corrosion in Example 3 of the present application;

[0031] Figure 7 This is a microstructure photograph of the Ti45Nb alloy sample after corrosion in the large deformation extrusion state of Example 3 of the present application;

[0032] Figure 8 This is a microstructure photograph of the annealed Ti45Nb alloy sample after corrosion in Example 4 of the present application;

[0033] Fig. 9 This is a microstructure photograph of the Ti45Nb alloy sample after corrosion in the large deformation extrusion state of Example 4 of the present application;

[0034] Fig.10 This is a microstructure photograph of the annealed Ti45Nb alloy sample after corrosion in Example 5 of the present application;

[0035] Fig.11 This is a microstructure photograph of the Ti45Nb alloy sample after corrosion in Example 5 of the present application. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0037] It should be noted that the term "include" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the existence of other identical elements in the process, method, article or device including its elements.

[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.

[0039] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0040] Example 1

[0041] The present application embodiment provides a metallographic corrosion method for Ti45Nb alloy, and the steps are as follows:

[0042] Sample treatment: 20mm×10mm×10mm samples of Ti45Nb alloy in annealed state and large deformation extrusion state were cut respectively, and their surfaces were first coarsely ground with 120 mesh, 240 mesh, 600 mesh, and 800 mesh water sandpaper in sequence, and then finely ground with 1200 mesh and 2000 mesh water sandpaper in sequence;

[0043] Then, the polished sample to be corroded is first polished with a diamond polishing spray with a particle size of 5 μm and a velvet polishing fabric to make the polished surface free of scratches caused by polishing. Then, the diamond polishing spray with a particle size of 3 μm and 1 μm is used in turn with a velvet polishing fabric to polish the sample to be corroded to make the polished surface reach a mirror effect.

[0044] Then the sample is cleaned and dried to obtain the sample to be corroded.

[0045] Preparation of metallographic etching solution: Take 75 ml of analytical pure hydrofluoric acid with a mass concentration of 40% and 25 ml of analytical pure nitric acid with a mass concentration of 68%. First, slowly pour the nitric acid into a beaker, then use a glass rod to drain the hydrofluoric acid slowly into the beaker containing nitric acid, and finally use a glass rod to stir the etching solution evenly to obtain the metallographic etching solution.

[0046] Metallographic corrosion: Dip the prepared metallographic corrosion liquid into absorbent cotton, clamp the absorbent cotton with the metallographic corrosion liquid with stainless steel pliers, and wipe the polished surface of the sample to be corroded continuously for 9 seconds for wiping corrosion; after the corrosion is completed, rinse with clean water (tap water or distilled water) within 2 seconds, then rinse with anhydrous ethanol, and then blow dry with a hair dryer to obtain a metallographic observation sample.

[0047] Example 2

[0048] This embodiment is based on Embodiment 1, and differs from Embodiment 1 in that:

[0049] In the metallographic etching solution preparation step, the ratio of the metallographic etching solution is: 73 ml of hydrofluoric acid and 27 ml of nitric acid;

[0050] In the metallographic etching step, the duration of the wipe etching is 6 seconds.

[0051] The remaining steps are the same as those in Example 1.

[0052] Example 3

[0053] This embodiment is based on Embodiment 1, and differs from Embodiment 1 in that:

[0054] In the metallographic etching solution preparation step, the ratio of the metallographic etching solution is: 77 ml of hydrofluoric acid and 23 ml of nitric acid;

[0055] In the metallographic etching step, the duration of the wipe etching is 12 seconds.

[0056] The remaining steps are the same as those in Example 1.

[0057] Example 4

[0058] This embodiment is based on Embodiment 1, and differs from Embodiment 1 in that:

[0059] In the metallographic etching solution preparation step, the ratio of the metallographic etching solution is: 76 ml of hydrofluoric acid and 24 ml of nitric acid;

[0060] The remaining steps are the same as those in Example 1.

[0061] Example 5

[0062] This embodiment is based on Embodiment 1, and differs from Embodiment 1 in that:

[0063] In the metallographic etching solution preparation step, the ratio of the metallographic etching solution is: 76 ml of hydrofluoric acid and 24 ml of nitric acid;

[0064] In the metallographic etching step, the duration of the wipe etching is 12 seconds.

[0065] The remaining steps are the same as those in Example 1.

[0066] Comparative Example

[0067] This comparative example is based on Example 1, and differs from Example 1 in that the metallographic etching solution preparation step is not performed; in the metallographic etching step, a conventional titanium alloy etching solution is used for the etching operation; specifically, a commercially available Korall reagent (ratio of HF 1ml, HNO3 3ml, H2O 100ml) is selected.

[0068] Test example

[0069] The metallographic observation samples obtained in Examples 1 to 5 of the present application and the comparative example were observed under a metallographic microscope for corrosion effects. The results are as follows: Figures 1 to 11 shown.

[0070] in, Figure 1 This is an optical microscope photograph (×100) of the Ti45Nb alloy sample after being corroded by a general titanium alloy corrosive solution in the comparative example. It can be found that it cannot clearly show the expected equiaxed grains.

[0071] Figure 2 This is a microstructure photograph (×100) of the annealed Ti45Nb alloy sample of Example 1 after corrosion. It can be seen that the grains are clear and the grain boundaries are distinct and easy to distinguish after corrosion.

[0072] Figure 3This is a microstructure photograph (×100) of the Ti45Nb alloy sample in the large deformation extruded state after corrosion in Example 1. It can be seen that the grains are clear after corrosion, and the grain direction is basically consistent with the extrusion direction.

[0073] Figure 4 This is a microstructure photograph (×100) of the annealed Ti45Nb alloy sample of Example 2 after corrosion. It can be seen that the grains are clear and the grain boundaries are distinct and easy to distinguish after corrosion.

[0074] Figure 5 This is a microstructure photograph (×100) of the Ti45Nb alloy sample in the large deformation extruded state after corrosion in Example 2. It can be seen that the grains are clear after corrosion, and the grain direction is basically consistent with the extrusion direction.

[0075] Figure 6 This is a microstructure photograph (×100) of the annealed Ti45Nb alloy sample of Example 3 after corrosion. It can be seen that the grains are clear and the grain boundaries are distinct and easy to distinguish after corrosion.

[0076] Figure 7 This is a microstructure photograph (×100) of the Ti45Nb alloy sample in the large deformation extruded state after corrosion in Example 3. It can be seen that the grains are clear after corrosion, and the grain direction is basically consistent with the extrusion direction.

[0077] Figure 8 This is a microstructure photograph (×100) of the annealed Ti45Nb alloy sample of Example 4 after corrosion. It can be seen that the grains are clear and the grain boundaries are distinct and easy to distinguish after corrosion.

[0078] Fig. 9 This is a microstructure photograph (×100) of the Ti45Nb alloy sample in the large deformation extruded state after corrosion in Example 4. It can be seen that the grains are clear after corrosion, and the grain direction is basically consistent with the extrusion direction.

[0079] Fig.10 This is a microstructure photograph (×100) of the annealed Ti45Nb alloy sample of Example 5 after corrosion. It can be seen that the grains are clear and the grain boundaries are distinct and easy to distinguish after corrosion.

[0080] Fig.11 This is a microstructure photograph (×100) of the Ti45Nb alloy sample in the heavily deformed extruded state after corrosion in Example 5. It can be seen that the grains are clear after corrosion, and the grain direction is basically consistent with the extrusion direction.

[0081] It can be seen that the embodiments of the present application can effectively corrode annealed and heavily deformed extruded Ti45Nb alloy samples, and the corrosion effect is good; in comprehensive comparison, the effect of the embodiment 1 is the best.

[0082] In summary, the embodiments of the present application provide a metallographic etching liquid and a corrosion method for Ti45Nb alloy. The metallographic etching liquid has a reasonable and simple component formula and is easy to prepare. It has a good corrosion effect on the Ti45Nb alloy and has high pollution-free corrosion efficiency. The Ti45Nb alloy after corrosion has clear grains and high surface contrast, and is easy to use. The corrosion method has a simple step flow, is easy to operate, has good stability, helps to improve the efficiency of the corrosion operation, and is beneficial to practical work applications.

[0083] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

Claims

1. A metallographic etching solution for Ti45Nb alloy, characterized in that: The raw materials include the following components by volume percentage: 73-77% of hydrofluoric acid and 23-27% of nitric acid.

2. The metallographic etching solution for Ti45Nb alloy according to claim 1, characterized in that: The hydrofluoric acid and the nitric acid are both analytically pure reagents.

3. A corrosion method for Ti45Nb alloy, characterized in that: The method adopts the metallographic etching solution as claimed in any one of claims 1 to 2, and comprises the following steps: Sample treatment: Take a Ti45Nb alloy sample, grind, polish, clean, and dry its surface in sequence to obtain a sample to be corroded; Preparation of metallographic etching solution: Take hydrofluoric acid and nitric acid, add hydrofluoric acid to nitric acid in proportion, and stir to obtain metallographic etching solution; Metallographic etching: The surface of the sample to be corroded is corroded using the metallographic etching solution, and then cleaned and dried.

4. The corrosion method for Ti45Nb alloy according to claim 3, characterized in that: In the sample processing step, when grinding, first use 120-800 mesh water sandpaper for coarse grinding, and then use 1200-200 mesh water sandpaper for fine grinding.

5. The corrosion method for Ti45Nb alloy according to claim 4, characterized in that: In the sample processing step, when grinding, first use 120 mesh, 240 mesh, 600 mesh, and 800 mesh water sandpaper for coarse grinding, and then use 1200 mesh and 2000 mesh water sandpaper for fine grinding.

6. The corrosion method for Ti45Nb alloy according to claim 3, characterized in that: In the sample processing step, during polishing, diamond polishing spray and velvet polishing fabric are used to polish the ground sample to be corroded.

7. The corrosion method for Ti45Nb alloy according to claim 6, characterized in that: In the sample processing step, when polishing, first use a diamond polishing spray with a particle size of 5 μm and a velvet polishing fabric to polish the grinded sample to be corroded, so that the polished surface has no scratches caused by grinding, and then use diamond polishing sprays with particle sizes of 3 μm and 1 μm in turn, in combination with velvet polishing fabric, to polish the sample to be corroded, so that the polished surface achieves a mirror effect.

8. The corrosion method for Ti45Nb alloy according to claim 3, characterized in that: In the metallographic etching step, absorbent cotton is used to dip into the prepared metallographic etching solution, and the surface of the sample to be corroded is wiped and corroded.

9. The corrosion method for Ti45Nb alloy according to claim 8, characterized in that: In the metallographic etching step, the wiping etching time is 6 to 12 seconds.

10. The corrosion method for Ti45Nb alloy according to claim 3, characterized in that: In the metallographic etching step, after the etching is completed, the surface is first rinsed with water, then rinsed with anhydrous ethanol, and then blown dry.